Neuroendocrine Carcinomas of the Canine Mammary Gland: Histopathological and Immunohistochemical Characteristics - Nakagaki, Karen Yumi Ribeiro; Nunes, Maíra Meira; Garcia, Ana Paula Vargas; De Brot, Marina; Cassali, Geovanni Dantas (Frontiers in Veterinary Science, 2021)
Invasive mammary carcinomas with neuroendocrine differentiation are rare in women and were reported only once in female dogs. For the present study, ten cases of solid mammary carcinoma positive for chromogramin A in immunohistochemistry were selected. Histopathological characteristics of these tumors were described and immunohistochemical evaluation was performed with chromogranin A, synaptophysin, CD56, NSE, PGP 9.5, pancitokeratin, Ki67, estrogen receptor (ER) and progesterone receptor (PR). The average animal age was 13.2 years old and the average tumor size was 4.8 cm. In total, 70% of the neoplasms were classified as grade III and 30% as grade II by the Nottingham histological grade system. High mitotic index was observed with a mean of 27.5 mitoses in 10 high magnification fields. Only one case showed typical carcinoid tumor characteristics. In addition, vascular invasion was shown in 3 tumors. All carcinomas were positive for chromogran A, while only two cases were reactive to synaptophysin. For PGP 9.2, NSE and CD56, we observed positivity of 100%, 90% and 70%, respectively, in the samples, being that no tumor was positive for all the neuroendocrine markers. All neoplasms showed ER and PR in at least 10% of neoplastic cells, while Ki67 varied from 29% to 95%, with mean mitotic index of 67%. Four of the ten animals died within one year of the tumor diagnosis. Neuroendocrine neoplasms occur in the canine mammary gland and are propably underdiagnosed. This is due to their non-specific morphological characteristics and the low use of neuroendocrine immunohistochemistric markers the diagnostic routine. More studies are necessary to determine the prognosis of this new histological type.